Feasibility Study to Produce Sound Barrier Brick Using Crumb Rubber - Siti Noreha Bt Che Bahrun, Siti Noreha (2010)
The wastes from automobile tires are increasing day by day. Some of them are reused in pavement material. Rubbers cannot be burned otherwise it will cause environmental issues. The dumping areas are insufficient as the wastes are increasing, led to mosquito breeding cases. In conjunction with that, a feasibility study was conducted to investigate potential of using crumb rubber in sound barrier wall application. The literature review has proved that rubberized-brick is not only has high porosity, it is also act as a good sound insulator. The properties of rubber enhanced the noise reduction as the noise is absorbed by the material. The combination of two sizes of crumb rubber which are 3.35 mm and 0.60 mm managed to produce greatest slump compared to other sizes. Fourthly percentage volumetric replacement of sand found to be optimum mixture. Hence, by adopting 40 % replacement of sand with combination crumb rubber with 3.35 mm and 0.6 mm, it was revealed that the brick was not only lighter but also stronger; 5.36 MPa. A prototype barrier wall of Im width xlm length was build using crumb rubber-added bricks. Similar, traffic noise level was generated, using a single source. The noise reduction was recorded by determining the difference of noise level at front and behind the wall and varied the location. It was proved that the noise reduction of the new potential barrier wall is much better than the conventional barrier wall using normal brick. From the study, the redundant tires can be reused to a newly product-based which is crumb rubber-added brick in sound barrier application. It is not only potential replace the conventional barrier wall but also solved two environmental problems, redundant waste tires and also traffic noise as well.